Analisis Kelayakan Pendirian Unit Produksi di Universitas (Studi Kasus Industri Minyak Atsiri) - Ahmad Mubin (Department Industrial Engineering, University of Muhammadiyah Malang, 2002)
The establishment of production unit requires fairly high investment, therefore to avoid the investment connducted which in fact will be unprofitable in the future, before implementing such investment, the comprehensive analysis or feasibility study is required, concerning marketing, technical financial management, and social-economyn alysis.From the result of feasibilitiy studythe level of feasibility for the establishment of production or business units is determined. In this case study, the subject of study is production of essential oil that serves as raw material for food, pharmacy, and parfume manufactures. Based on the analysis result of market and marketing aspects, as well as technical and Technology aspects, it was ndicated that the proposal of production unitestablishment feasible to beaccepted. Likewise, the result of financial analysis with the methods of Net present value, Profitability Index(B /C ratio), Internal Rate of Return and payback period,indicated that the proposal of production unitestablishmeint is feasibleto be accepted.